THE INFLUENCE OF TRAINING, EDUCATION AND MOTIVATION ON THE PERFORMANCE OF CULTURE AND TOURISM EMPLOYEE SAMOSIR DISTRICT - Annevelin Naibaho; Sugih Arto Pujangkoro; Iskandarini (International Journal of Economic, Business, Accounting, Agriculture Management and Sharia Administration (IJEBAS), 2023)
This study aims to determine the effect of training, education and motivation on the performance of employees of the Samosir Regency Culture and Tourism Office. This study used primary data obtained by distributing questionnaires to 80 respondents who were selected using a census technique. The variable measurement scale used in this study uses a Likert scale which functions to measure variable indicators that produce ordinal data. The results showed that training had an effect on Employee Performance at the Samosir Regency Culture and Tourism Office, education had an effect on Employee Performance at the Samosir Regency Culture and Tourism Office, motivation had an effect on Employee Performance on the Samosir Regency Culture and Tourism Office and training, education, and motivation had an effect on Employee Performance on Samosir Regency Culture and Tourism Office.